Knowledge and attitudes of nurses towards using study results in everyday clinical practice – preliminary report - Gotlib, Joanna; Belowska, Jarosława; Panczyk, Mariusz; Sienkiewicz, Zofia; Wójcik, Grażyna (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Background. It is necessary that nurses use up-to-date study results in their everyday practice in order to provide efficient and safe nursing care of highest quality standards. Aim. The aim of the study was to analyse the knowledge and attitudes towards EBNP. Material and methods. Bachelor’s degree students. A majority of the study population worked in the public sector, as a nurse at a teaching hospital. A pilot study. Qualitative study, structured interview, extended focus. Qualitative analysis of the study results. Results. 20 Bachelor’s degree students. Mean age — 43 years, mean length of service — 17 years. Nobody defined the acronyms EBM and EBP correctly. The nurses mentioned the following journals most often: “Impulse” and “Magazine for Nurses and Midwives”. Only 2 nurses participated in a development of procedures in their workplace. The following factors were most often indicated as those that limit the possibility of using EBNP: no time, insufficient knowledge of English and access to the Internet, working at the position that makes taking decisions impossible. Conclusions. 1. The level of knowledge of EBNP were insufficient. 2. The boundaries limiting the use of the EBNP were objective and they require system changes with reference to the organization of work and the system of continuing education. 3. It is necessary to expand the skills of nurses with reference to searching for scientific evidence and assessing its reliability. 4. It is necessary to expand the knowledge of nurses with reference to the benefits of using current study results in everyday clinical practice.